K. Popper’s political philosophy and paradox of freedom - Patkauskaitė, Jūratė (Problemos, 1995)
K. Popper’s “Open Society and Its Enemies” is analysed in the paper. K. Popper has claimed his book to present by itself not only the research into social knowledge and philosophy of history, but a sort of political philosophy as well. K. Popper opposes protectionist theory of the state to the theories in which state becomes the object of divination. However, K. Popper does not welcome the principle of strict non-interference. He points out that freedom is unthinkable, if it is not protected by state. The matter is that unlimited freedom acts upon itself.